Análise das matrizes sobre associativismo civil norteadoras da formação de trabalhadores para Ongs - Perez, Deivis [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2013)
This article presents research that aimed to discuss the theoretical frameworks about civil associativism prescribed by the trainers of non-governmental organizations (NGOs) workers. The requirements for civil associations made by trainers were analyzed based on two data and reference categories, named empirical and analytical. The empirical categories emerged from the data collected by means of interviews with trainers and also examining the documents that guided the course. The analytical categories were constructed from the literature review on the approaches of civil associations, which are: North American Third Sector Approach; Critical Approach to the Third Sector and Social Local Development (DSL in the Portuguese acronym). The study presents indications that could support the development of other research on the topic and, mainly academic knowledge for further development of new training processes for NGO workers.

Este artigo apresenta uma pesquisa que teve como objetivo discutir as matrizes teóricas sobre associativismo civil prescritas pelos formadores de um curso de capacitação de trabalhadores para a atuação em organizações não governamentais (ONGs). As indicações sobre associativismo civil realizadas pelos formadores foram analisadas por meio da circunscrição de duas categorias de referências e dados, nomeadas empíricas e analíticas. As categorias empíricas emergiram dos dados recolhidos em campo, nas entrevistas semidiretivas com os formadores e, também, do exame dos documentos norteadores do curso. As categorias analíticas foram construídas por intermédio da revisão da literatura sobre as abordagens de associativismo civil, que são: abordagem norte-americana de Terceiro Setor; abordagem crítica ao Terceiro Setor e desenvolvimento social local (DSL). Ao final do artigo há indicações que poderão apoiar o desenvolvimento de outras pesquisas sobre o tema e, principalmente, saberes acadêmicos que poderão auxiliar o desenvolvimento ulterior de processos formativos de trabalhadores para ONGs.
Analysis of the guidelines about civil associations for the training of ngos workers
Keywords: Worker training; Civil associations; Non-governmental organizations; Formação de trabalhadores; Associativismo civil; Organizações não governamentais